COMPARATIVE CLINICAL STUDY OF THE HAEMORRHOIDECTOMY AND KSHARASUTRA TRANSFIXATION WITH TWO INCISIONS IN THE MANAGEMENT OF PROLAPSED HAEMORRHOIDS - Bhagyalaxmi, Durgam; Dattatreya Rao, S. (International Journal of Ayurveda and Pharma Research, 2015)
Kshara-sutra transfixation (KST) is one of the most efficacies and worldwide accepted treatments of hemorrhoids because of its effectiveness and less complication rate. Hemorrhoidectomy (HMD) is the procedure of choice for treatment of grade three and four hemorrhoids, which is a painful method for a relatively benign disease. There are a few studies available analyzing the effectiveness of Ksharasutra transfixation as an initial treatment for grade three and four symptomatic internal hemorrhoids.Arsha (hemorrhoids) is engorgement of the hemorrhoidal venous plexus, characterized by bleeding per rectum, constipation, pain, prolapse and discharge. It is manifested due to improper diet, prolonged standing and faulty habits of defecation causing derangement of Tridosha. The Kshara sutra Transfixation method in Arshas was studied in comparison with hemorrhoidectomy. Kshara sutra trans-fixation with two incision on the bulged mass in Arshas was employed in 15 patients, and 17 patients were dealt with hemorrhoidectomy. The study revealed a better result of the Kshara sutra Transfixation with two incision on the bulged mass group in comparison with hemorrhoidectomy. The observations revealed that maximum advantages like minimum hospital stay, no bleeding during or after operation, no post-operative anal stenosis, a low cost-effective and more acceptable to different categories of people, etc. were recorded in the Kshara sutra-treated group. Statistically, Kshara-sutra Transfixation for Arshas was found to be highly significant (There are significant difference among the PODS with reference to the mean grades. The corresponding F-value is given by 7.486535 which is highly significant at 1% level) and effective management. No adverse effects were noted during the follow-up period.